Metal‐coordinated amino acid/peptide/protein‐based supramolecular self‐assembled nanomaterials for anticancer applications - Maryam Shabbir; Atia Atiq; Jiahua Wang; Maria Atiq; Nyla Saeed; Ibrahim Yildiz; Xuehai Yan; Ruirui Xing; Manzar Abbas (Aggregate)
Abstract Biomolecules with metals can form supramolecular nanomaterials through coordination assembly, opening new avenues for cancer theranostics and bringing unique insights into personalized nanomedicine. These biomaterials have been considered versatile and innovative nanoagents due to their structure‒function control, biological nature, and simple preparation methods. This review article summarized the recent developments in multicomponent nanomaterials formed from metal coordination interactions with amino acids, peptides, and proteins, together with anticancer drugs, for cancer theranostics. We discussed the role of functional groups anchored in building blocks for coordination interactions, and subsequently, the types of interactions were examined from a structure‒function perspective. Amino acids with different metals and anticancer drugs forming supramolecular nanomaterials and their anticancer mechanisms were highlighted. Peptides with different metals and anticancer drugs, proteins with metals and anticancer drugs used for material formations, and anticancer activity have been discussed. Ultimately, the conclusion and future outlook for multicomponent supramolecular nanomaterials offer fundamental insights into fabrication design and precision medicine.